Consumer purchase behavior for fresh milkfish in Davao City - Ednalgan, Lady Lard Janica S.
Fish is a vital food source for people. Among which, milkfish is one of the most consumed in the world. In the Philippines, milkfish is an important component of the fisheries sector which significantly contributed to the country's output, employment, public revenues and nutrition. Amidst all these opportunities, the changing consumption pattern and habits of the Filipinos has been a major concern of milkfish producers and marketers. This study assists in the understanding of consumer buying behavior among income class group towards fresh milkfish in Davao City. This information is important in guiding various sectors in planning and developing milkfish production. To achieve this, the study examined 101 households in Davao City which were classified into income class groups. Using weighted means, the study revealed that price, safety and accessibility of the place are the important factors that consumers consider in buying milkfish. Factors such as nutrition, convenience of preparation, lifestyle, origin of the milkfish, and availability of supply proves to be moderately important for consumers. In terms of factors that are significantly different across income class groups, group AB (higher income class) and DE (lower income class) are significantly different in attributing importance to convenience and lifestyle. The choice of place purchase , freshness of the milkfish, cleanliness of the area, smell of the place and quality of the service are the most considered factors by the respondents in the purchase of milkfish. Meanwhile, using one way ANOVA and Tukey Multiple Comparison Test results revealed that factors such as good display of milkfish, speed of service and quality of service are significantly different between AB and DE income class groups. It was further revealed that majority of the respondents prefer to purchase fresh milkfish in public wet markets during weekends.